Impact of a Preclinical Elective on Medical Student Performance on an Anesthesiology Simulation Scenario - Sawka DM; Kendall MC; Diorio MS; Derias NO; Rajaee A; Ji C; Asher SR (Advances in Medical Education and Practice)
Danielle M Sawka, Mark C Kendall, Matthew S Diorio, Nardin O Derias, Arezoo Rajaee, Chao Ji, Shyamal R Asher The Warren Alpert Medical School of Brown University, Providence, RI, 02903, USACorrespondence: Shyamal R Asher, Anesthesiology, Rhode Island Hospital, 593 Eddy Street, Davol 129, Providence, RI, 02903, USA, Tel +1 401-527-4775, Email ashershy@gmail.comIntroduction: Preclinical medical students often have minimal exposure to topics within the field of anesthesiology. As efforts to expand clinical exposure in the preclinical curriculum are increasing, there remains an unawareness of which education topics are still undervalued. This study is the first application of an anesthesiology simulation in the medical student population that incorporates objective performance evaluation that aims to identify key areas of clinical learning growth and gaps within anesthesiology following a semester-long elective.Methods: Our study population consisted of 14 first- and 2 second-year medical students interested in a career in anesthesiology and enrolled in an anesthesia preclinical elective at a single-institution. The students were tested on the same clinical scenario graded based on a standardized rubric prior to and after the completion of the anesthesia preclinical elective. Differences in individual simulation scores were analyzed using t-test, or Wilcoxon signed-rank test for paired samples.Results: The students had a statistically significant increase in individual total scores (p < 0.001), with the strongest improvements in basic induction skills (p < 0.001) and response to hemodynamic changes (p < 0.001) after completion of the elective. There was no significant improvement in PACU management skills (p = 0.184) after completion of the elective, although the small sample size limits statistical power.Conclusion: This first application of anesthesia-based simulation training with performance scoring in medical students highlights the possible need for targeted early intervention in post-operative management for medical students interested in a career in anesthesiology.Keywords: anesthesia, elective, PACU, preclinical medicine, VAST